TEKNIK PEMBENIHAN IKAN KOKI (Carassius auratus) DI INSTALASI PERIKANAN BUDIDAYA KEPANJEN MALANG - Windarti Windarti; Nur Maulida Safitri; Farikhah Farikhah (Universitas Mataram, 2024)
Kepanjen Aquaculture Installation (IPB) is one of the fish growers located in Kepanjan, Malang district. This research focuses on the management of cook fish filling techniques with the aim of ensuring that the filling technique carried out by the community can be done well and get quality seed yields. This study took samples from the Plant for Cultivated Fisheries (IPB) that were carried out for 40 days using samples of 5 different types of cooked fish. This method of research uses an explorative descriptive approach, namely by describing a result in research, but the result of research is not used as a general conclusion. There are several measurement indicators performed in the filling technique: 80% Hatching rate (HR), Survival Rate (SR) 89,01%, Daily Growth Rate Calculation (SGR) with a value of 0.012133 grams/day, Fekundity of 785 grains, Absolute Weight and Absolute Length measurements, Food Supply Management and Water Quality Management. It is driven by the level of water quality, temperature as well as excellent pool management installation. As well as the pesticide and disease treatment techniques that are performed are very helpful at the time of the rejuvenation process.